Silver-modified porous 3D nitrogen-doped graphene aerogel: Highly efficient oxygen reduction electrocatalyst for Zn−Air battery. (10th April 2019) - Hu, Jie; Shi, Ziwei; Wang, Xueqian; Qiao, Huici; Huang, Hao
Abstract: Developing highly efficient electrocatalyst is crucial to improve the efficiency of oxygen reduction reaction for Zn-air battery. Herein, Ag-modified porous 3D nitrogen-doped graphene aerogel is synthesized by one-step hydrothermal method for promoting the electrocatalytic performance and stability toward oxygen reduction reaction. Interestingly, in this study, N doping process, reduction of AgNO3 and graphene oxide, and the three-dimensional self-assembly can be finished during the hydrothermal synthesis at the same time. The obtained Ag-modified 3D nitrogen-doped graphene hybrid presents an interconnected 3D porous framework and Ag nanoparticles homogeneously distribute on the inner and surface of 3D N-doped graphene networks. The unique structure results in excellent oxygen reduction reaction catalytic activity with a superior stability to commercial 20 wt% Pt/C. The high electrochemical activity and durability of the hybrid is also confirmed in Zn-air batteries that outperform Pt/C in discharge voltage plateau and long-term durability, showing a promising oxygen reduction catalyst for Zn-air batteries.